A influência do barulho da torcida na tomada de decisão de um árbitro - Calmanovici, Samuel Felipe Leal [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The role of a soccer referee is to promote order and justice in the match, but for being a much more discreet element than the players, despite being fundamental, it is little studied. Due to the fact that the referee does not have ideal courses for training, it is noted that the dramatic effect generated by the noise of the crowd has a great influence on the decision-making of those responsible, generating errors that affect the order and justice of the match. , which has a crowd of noisy fans present in the stadium. Therefore, the objective of the research is to study materials related to the theme, capable of providing an analysis to verify how and how much the noise of the crowd influences the technical performance of a soccer referee. The research method that was used is a bibliographical and documental review, researching contents of the scientific community so that it was possible to go deeper into the subject with different interpretations and known considerations. Thus, it was found that the criteria for direct release while they are acting and there is noise in the stadium, and cases that cause errors can be observed, possibly due to the deconcentration generated by the noise made by the fans. Thus, it was possible that noise is a relevant variable to define football errors, which can generate errors due to changes in the levels of concentration, focus and attention. Thus, refereeing errors can be crucial to define the final result of the match. Therefore, it is necessary that more studies are carried out related to refereeing in sports and football, seeking to understand these characters, their actions and seeking to provide greater support and emotional balance so that they know how to deal with different moments provided by sport.

A função de um árbitro de futebol é promover ordem e justiça na partida, mas por ser um elemento bem mais discreto que os jogadores, apesar de fundamental, é pouco estudado. Em função do árbitro não ter cursos ideais para a formação é notado que o efeito dramático causado pelo barulho da torcida possui grande influência na tomada de decisão dos árbitros, gerando erros técnicos que prejudicam a ordem e justiça da partida, geralmente esses erros beneficiam o time mandante, que possuem uma multidão de torcedores barulhentos presentes no estádio. Logo, o objetivo da pesquisa é estudar materiais referentes à temática, capazes de fornecer uma análise para verificação de como e quanto o barulho da torcida influencia no desempenho técnico de um árbitro de futebol. O método de pesquisa que foi utilizado é a revisão bibliográfica e documental, pesquisando conteúdos da comunidade científica para que fosse possível o aprofundamento no tema com diferentes interpretações e considerações confiáveis. Deste modo, foi encontrado que os árbitros sofrem influência direta enquanto estão atuando e existe barulho no estádio, podendo ser observados casos que ocasionam erros, propiciados, possivelmente, pela desconcentração gerada diante do barulho realizado pelos torcedores. Assim, foi possível entender que o barulho é uma variável extremamente relevante para árbitros de futebol, podendo gerar erros técnicos devido a alteração nos níveis de concentração, foco e atenção. Deste modo, os erros da arbitragem podem ser cruciais para definir o resultado final da partida. Por isso, é preciso que sejam realizados mais estudos relacionados à arbitragem no meio esportivo e futebolístico, buscando entender esses personagens, suas atuações e, buscar proporcionar maior apoio e equilíbrio emocional para que saibam lidar com os diversos momentos proporcionados pelo esporte.
The influence of fans noise on the decision making of a football referee
Keywords: Soccer; Referee; Decision making; Futebol; Árbitro; Tomada de decisão